CHE : the bulletin of the Campaign for Homosexual Equality. (Manchester : CHE, 1975)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks?Redactie : PO Box 427, 28 Kennedy street, Manchester M60 2EL
Engels
Periodiek